Curving the Solvatochromic Tendency of Pyridinium Phenolate Sensors by Increasing Their Sensitivity to Solvent Polarizability - Aliaga-Vidal, C; Aliaga-Vidal, C; Dominguez-Caru, M; Vidal-Palomo, M; Vidal-Palomo, M (Elsevier B.V., 2024)
Three classic pyridinium-phenolate sensors exhibiting negative solvatochromism were modified by the addition of a 1,4-phenylene linker, resulting in three derivatives displaying inverted solvatochromism, with inversion points observed in polar solvents, such as DMSO. This study shows that the 1,4-phenylene linker is essential for the inverted solvatochromism of this sensor class. DFT calculations, multiparametric regressions, and molecular dynamics simulations in methanol suggest that the inversion is caused by increased sensitivity to the polarizability of the solvent and the loss of hydrogen bonds in solution. Finally, the present series presents a method for transforming negative solvatochromic pyridinium-phenolates into sensors displaying inverted solvatochromism by adding the 1,4-phenylene unit to the π-linker between the donor-acceptor pair. © 2023 Elsevier B.V.